A Teacher Training on Digital Assessment Strategies for Meaningful Learning Outcomes at Buranakarn Suksa Witya School, Thailand - Aziez, Feisal; Sadeli, Elly Hasan; Anjarani, Shelia; Hawanti, Santhy; Setianti, Dika; Rinjani, Rinjani (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2024)
Technological advancements have had a profound impact on the education sector around the globe including in Thailand and other developing countries.  as in many other developing countries, there are major challenges in adapting with the rapid development of technology. The school where the community service was held also faced similar issues. With an innovative approach through assessment training using technology, this community engagement activity is expected to be a positive step towards educational transformation, particularly in the southern part of Thailand. With the active involvement of teachers as well as full support from related parties, we can create a learning environment that is more dynamic, relevant, and globally competitive. A pre-test and a post-test were conducted at the beginning and the end of the training to measure teachers’ understanding in implementing digital assessment strategies. By equipping teachers with the knowledge and skills to implement digital assessment strategies, the training has had a measurable impact on professional development and instructional practices. In addition, the training provide access to further consultation or guidance, participants can feel supported and more confident in applying their learning in the classroom. The results of the pre- and post-training survey demonstrated a substantial improvement, averaging 51.3% increase across all survey items. This indicates the positive impact of the training in enhancing teachers' competencies in integrating technology into their assessment practices.  Moving forward, schools in rural Thailand can apply the lessons learned from this workshop to enhance their own educational outcomes. Keywords: teacher training; digital assessment strategies; southern Thailand Abstrak: Dalam era globalisasi yang semakin cepat, pendidikan adalah salah satu aspek yang paling terpengaruh oleh perkembangan teknologi. Di Thailand Selatan, seperti di banyak negara berkembang, ada tantangan besar dalam dalam beradaptasi dengan perkembangan teknologi yang pesat. Sekolah tempat dimana program pengabdian kepada masyarakat ini dilaksanakan juga menghadapi masalah serupa. Dengan pendekatan inovatif melalui pelatihan penilaian menggunakan teknologi, kegiatan keterlibatan masyarakat ini diharapkan menjadi langkah positif menuju transformasi pendidikan di wilayah Thailand Selatan ini. Dengan keterlibatan aktif dari para guru serta dukungan penuh dari pihak terkait, kita dapat menciptakan lingkungan pembelajaran yang lebih dinamis, relevan, dan kompetitif secara global. Pre-test dan post-test dilakukan di awal dan akhir pelatihan untuk mengukur pemahaman guru dalam menerapkan strategi penilaian digital. Selain itu, pelatihan menyediakan akses ke konsultasi atau bimbingan lebih lanjut, sehingga peserta merasa didukung dan lebih percaya diri dalam menerapkan pembelajaran mereka di kelas. Setelah pelatihan selesai, kedua pihak melakukan evaluasi menyeluruh untuk mengukur keberhasilan, mengidentifikasi area yang perlu perbaikan, dan memberikan dampak yang lebih positif dalam jangka panjang.Kata kunci: pelatihan guru; strategi penilaian digital; thailand selatan